Prevalence of hypobetalipoproteinemia and related psychiatric characteristics in a psychiatric population: results from the retrospective HYPOPSY Study - Bertrand Cariou; Gaëlle Challet-Bouju; Céline Bernard; Marie Marrec; Jean-Benoit Hardouin; Charlotte Authier; Kalyane Bach-Ngohou; Christophe Leux; Matthieu Pichelin; Marie Grall-Bronnec (Lipids in Health and Disease, 2018)
Abstract Background Hypobetalipoproteinemia (HBL) is defined by plasma concentrations of LDL-cholesterol (LDL-C) lower than the fifth percentile for age and sex. Several psychiatric symptoms have been reported in association with HBL. The objective was to assess the prevalence of primary HBL in patients hospitalized in a psychiatric population and to better characterize the related psychiatric disorders. Methods HYPOPSY is a retrospective study including 839 adults hospitalized in the Psychiatry department of Nantes University Hospital during the year 2014, except patients with eating disorders. The prevalence of primary HBL was defined by a plasma LDL-C concentration ≤ 50 mg/dL. Secondary causes of HBL were excluded after a review of medical records (n=2). Related-psychiatric disorders in patients with and without HBL were recorded using the ICD-10 classification. Results Twenty cases of primary HBL (mean [SD] LDL-C: 42 [7] mg/dL) were diagnosed, leading to a prevalence of 2.39%. In comparison, the prevalence of HBL in a healthy control population was 0.57%. Psychiatric patients with HBL were characterized by a higher frequency of schizophrenia (p=0.044), hetero-aggression (p=0.015) and pervasive and specific developmental disorders (including autism) (p=0.011). Conclusions The prevalence of HBL is 4-fold higher in psychiatric than in general population. More specifically, some statistically significant associations were found between low LDL-C concentrations and schizophrenia, autism and hetero-aggression. These data reinforce the hypothesis for a link between genetically low LDL-C levels and psychiatric disorders.